Endocultivation: continuous application of rhBMP-2 via mini-osmotic pumps to induce bone formation at extraskeletal sites. Issue 5 (May 2017) - Beck-Broichsitter, B.E.; Becker, S.T.; Seitz, H.; Wiltfang, J.; Warnke, P.H.
Abstract: The continuous presence of recombinant human bone morphogenetic protein 2 (rhBMP-2) inside a scaffold may be crucial to the outcome in bone tissue engineering. This study investigated whether the release of the growth factor rhBMP-2 via different continuous application schemes influences histomorphological aspects of the hard and soft tissues induced. Three-dimensionally printed hydroxyapatite scaffolds were implanted into one latissimus dorsi muscle of 42 female Lewis rats. Simultaneously implanted mini-osmotic pumps were used to provide a continuous application of rhBMP-2 over 1, 2, or 4 weeks (total dose 200 μg). A reference group received rhBMP-2 at the time of implantation only, and a control group received only block implantation. Bone density and histological examinations were performed after 8 weeks. No significant difference in bone density was found between the groups; however, the blood vessel count differed significantly between the groups receiving continuous treatments and both the control group and simultaneous rhBMP-2 treatment group ( P < 0.0001). Soft tissue types were distributed differently among the study groups. RhBMP-2 application via mini-osmotic pumps is as suitable for inducing bone formation as a single application at the time of implantation. The time interval over which rhBMP-2 was administered had no impact on the amount of new bone formation, probably due to the study duration and low local concentrations of growth factor.